Behind the Mask and Look Me in The Eye: Exploring the Relation of Self-Confidence With Conformity in Today’s Teenagers - Hapsari Lily Dewanti (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Teenagers are particularly susceptible to conformity and apparently self-confidence plays a significant role in how teenagers make individual choices.Drawing on the relevance between the two, this creative project explores today’s teenagers’ manner on conformity and assesses how teenagers’ self-confidence is related to their decision to conform or not to conform. To understand how self-confidence and conformity relate to each other deeper, I use Herbert Kelman’s theory of the three processes of attitude change in conformity and Mastuti’s theory of self-confidence on self-confidence. This creative project is two plays of 30 minute play which explores about the same issue but is seen from different angle of perspectives. Behind the Mask focuses on how a teenager who has lack of self-confidence conforms to her peer group while Look Me in the Eye focuses on how a teenager who has self-confidence conforms to her peer group.Showing different angle of perspectives help me conveying my purpose of writing the plays which is to help teenagers understand that conformity in daily life is inevitable and how their self-confidence plays an important role so that they will not get influenced by conformity easily.For the genre, the plays use realistic drama as the genre conventions suit the style of my plays which portrays a conflict that happens in teenagers’ daily life in a realistic way.